2019
DOI: 10.1016/j.syapm.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and distribution of Bradyrhizobium symbionts nodulating cowpea (Vigna unguiculata L. Walp) and their association with the physicochemical properties of acidic African soils

Abstract: In the N 2 -fixing symbiosis, the choice of a symbiotic partner is largely influenced by the host plant, the rhizobial symbiont, as well as soil factors. Understanding the soil environment conducive for the survival and multiplication of root-nodule bacteria is critical for microbial ecology. In this study, we collected cowpea-nodules from acidic soils in Ghana and South Africa, and nodule DNA isolates were characterized using 16S–23S rRNA-RFLP, phylogenetic analysis of housekeeping and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…(Mohammed, Jaiswal and Dakora 2018) and Puozaa et al . (Puozaa, Jaiswal and Dakora 2019) also reported that soil pH and mineral nutrients can influence the diversity of bradyrhizobial populations in South African and Ghanaian soils, and found that N, P and Na concentrations could specifically influence South African isolates. The results of this study also suggested that bradyrhizobial distribution in soil was strongly controlled by soil physico-chemical properties such as pH, and mineral nutrients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…(Mohammed, Jaiswal and Dakora 2018) and Puozaa et al . (Puozaa, Jaiswal and Dakora 2019) also reported that soil pH and mineral nutrients can influence the diversity of bradyrhizobial populations in South African and Ghanaian soils, and found that N, P and Na concentrations could specifically influence South African isolates. The results of this study also suggested that bradyrhizobial distribution in soil was strongly controlled by soil physico-chemical properties such as pH, and mineral nutrients.…”
Section: Discussionmentioning
confidence: 93%
“…Cowpea is one of the most important indigenous legume crops in Africa, with both wild and cultivated forms growing across the continent (Mohammed, Jaiswal and Dakora 2018). West Africa is the centre of origin of this crop (Jaiswal and Dakora 2019; Puozaa, Jaiswal and Dakora 2019). Cowpea can meet 66% to 96% of its N nutrition from symbiotic fixation (Jaiswal and Dakora 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puozaa et al . 3,19 and Ndungu et al . 29 also recently reported a significant influence of soil mineral nutrients on the bradyrhizobial distribution in some African soils, which all indicate the roles of these soil factors on the occurrence and persistence of rhizobial types in different geographic areas.…”
Section: Discussionmentioning
confidence: 95%
“…Novel markers such as ftsA gene provide congruent phylogenies to those derived from recA and glnII gene sequences (Kalita and Malek, 2019). Bradyrhizobium diversity knowledge has expanded recently with studies from native legumes in Africa (Gronemeyer et al, 2017; Jaiswal and Dakora, 2019; Puozaa et al, 2019), from Brazilian and Indian Chamaecrista (Santos et al, 2017; Rathi et al, 2018), from threatened native species in Brazil (Fonseca et al, 2012), from Genisteae plants in Poland (Kalita and Malek, 2017), indigenous trees in China (Yao et al, 2015) as examples. In addition, new bradyrhizobial species have been reported as well (Yao et al, 2015; Araujo et al, 2017; Gronemeyer et al, 2017; Helene et al, 2017; Ahnia et al, 2018; Bunger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%